innovation research award - Front Cover in Scientific journal as Front cover of the Journal of Inorganic Biochemistry, for the volume 237 - Drouza, Chryssoula (My University, 2026)
my research was awarded for it innovation by presented as Front cover of the Journal of Inorganic Biochemistry, for the volume 237 for the research titledQ: "{Binuclear VIV/V, MoVI and ZnII - hydroquinonate complexes: Synthesis, stability, oxidative activity and anticancer properties"
Keywords: Natural sciences